Coupling the dual isotopes of water (δ 2H and δ 18O) and nitrate (δ 15N and δ 18O): a new framework for classifying current and legacy groundwater pollution - Julie N Weitzman; J Renée Brooks; Paul M Mayer; William D Rugh; Jana E Compton (Environmental Research Letters, 2021)
Nitrate contamination of groundwater is a concern globally, particularly in agricultural regions where decades of fertilizer nitrogen (N) use has led to a legacy of N accumulation in soils and groundwater. Linkages between current management practices and groundwater nitrate dynamics are often confounded by the legacy effect, and other processes unrelated to management. A coupled analysis of dual stable isotopes of water ( δ H _2 O = δ ^2 H and δ ^18 O) and nitrate ( δ NO _3 ^− = δ ^15 N and δ ^18 O) can be a powerful approach to identify sources and processes responsible for groundwater pollution. To assess how management practices impact groundwater nitrate, we interpreted behavior of δ H _2 O and δ NO _3 ^− , together with nitrate concentrations, in water samples collected from long-term monitoring wells in the Southern Willamette Valley (SWV), Oregon. The source(s) of nitrate and water varied among wells, suggesting that the nitrate concentration patterns were not uniform across the shallow aquifer of the valley. Analyzing the stability versus variability of a well’s corresponding δ H _2 O and δ NO _3 ^− values over time revealed the mechanisms controlling nitrate concentrations. Wells with stable δ H _2 O and δ NO _3 ^− values and nitrate concentrations were influenced by one water source with a long residence time and one nitrate source. Variable nitrate concentrations of other wells were attributed to dilution with an alternate water source, mixing of two nitrate sources, or variances in the release of legacy N from overlying soils. Denitrification was not an important process influencing well nitrate dynamics. Understanding the drivers of nitrate dynamics and interaction with legacy N is crucial for managing water quality improvement. This case study illustrates when and where such coupled stable isotope approaches might provide key insights to management on groundwater nitrate contamination issues.